Distribución temporo-espacial y mortalidad por Covid-19 de la población perteneciente a la provincia de Zamora Chinchipe de los años 2020 al 2022 - Torres Solórzano, Paola Belén (2024)
Covid-19, infection by Sars-Cov-2, affects the respiratory system and has high transmissibility; its morbimortality is high in older adults and men, being considered possible risk factors. The aim of this research was to determine the epidemiological situation of Covid-19 in the population of the province of Zamora Chinchipe based on its temporal-spatial distribution and mortality in the years 2020 - 2022. A quantitative, cross-sectional approach was applied, with a sample of 2802 cases of disease and death collected from the open data databases of the Ministry of Public Health, its analysis was performed using customized tables with the SPSS statistical package and the determination of mortality rates was done in Excel using the formula of number of deaths divided for the total population by 10 000, in certain populations that did not reach 10 000 inhabitants was multiplied for 1000. It was obtained that 90.5% of cases occurred in men and 68.6% occurred between 20 and 49 years of age, the trends from 2020 to 2022 in Zamora Chinchipe tend to decrease, the highest peak was in 2020 in Zamora with 31.6% of that year. People aged 65 had a mortality rate of 5.4; men had a mortality rate of 9; Chinchipe's mortality rate was higher at 7.5. It was concluded that Covid-19 is more frequent in men and in the age of 20 to 49 years; its trend from 2020 to 2022 decreases in Zamora Chinchipe; its highest mortality rate was 65 years or more and in men, Chinchipe is the canton with the highest mortality rate